Neuropsychology and Therapeutic Techniques: Influence on Patients with Mood Disorders - Nur Rohmatillah; Agustin Andhika Putri; Catur Budi Susilo; Budhy Ermawan (Yayasan Adra Karima Hubbi, 2025)
Mood disorders, including depression and bipolar disorder, are pervasive mental health conditions that significantly impair emotional regulation, cognitive functioning, and daily life. Advances in neuropsychology have provided valuable insights into the neural mechanisms underlying mood disorders, yet their integration into therapeutic interventions remains underexplored. This study investigates the influence of neuropsychological principles on the effectiveness of therapeutic techniques in managing mood disorders. The research aimed to evaluate the impact of neuropsychology-informed therapeutic techniques on emotional regulation, cognitive performance, and symptom severity in patients with mood disorders. A mixed-methods approach was employed, combining a randomized controlled trial (RCT) with qualitative interviews. The study involved 120 participants diagnosed with mood disorders, divided into intervention and control groups. The intervention group received a 10-week program integrating cognitive-behavioral therapy (CBT), mindfulness-based techniques, and neurofeedback training, while the control group received standard care. Findings revealed significant improvements in emotional regulation and cognitive functioning among the intervention group compared to the control group (p < 0.01). Participants in the intervention group also reported reduced symptom severity and increased resilience.